Penentuan Jumlah Kebutuhan Tenaga Kerja pada Stasiun Kerja Composer Dengan Menggunakan Metode Work Sampling di PT. Asia Forestama Raya - Fiky Two Nando; Widya Laila (Journal of Engineering Science and Technology Management (JES-TM), 2022)
The purpose of this study was to determine the average productive percent of operators so that they can determine the standard time required for operators to carry out their work at PT. Asia Forestama Raya Composer station, and to find out the amount of manpower needed at this station.  The method used in this study is the Work Sampling Method, this method is a work technique to conduct a large number of observations on the work activities of machines, processes and workers or operators. The sample used in this study were workers or operators at the Composer work station. Composer work station is a work station consisting of 12 Cast Builder machines with each machine consisting of 5 operators, the work of this station is to connect plywood sheets according to standard sizes. Based on the results of data processing that has been carried out in this study, it can be concluded that the average working productive percent of all operators is 94.087%. The standard time required for the work process on the Cor Builder machine is 11.3 minutes/m3, and the amount of labor required at the Composer work station initially amounted to 5 people (with details of 2 people as Cor Builder machine operators, 2 people as repair as well as inspection, and 1 person as waste disposal), to 7 people (with details of 2 people as Cor Builder machine operators, 4 people as repair and inspection, and 1 person as waste disposal.